Responsibility and liability in the context of transboundary movements of hazardous wastes by sea : existing rules and the 1999 Liability Protocol to the Basel Convention /: existing rules and the 1999 Liability Protocol to the Basel Convention. ([2014]) - Albers, Jan
No abstract available